2013
DOI: 10.1371/journal.pone.0063148
|View full text |Cite
|
Sign up to set email alerts
|

Sago-Type Palms Were an Important Plant Food Prior to Rice in Southern Subtropical China

Abstract: Poor preservation of plant macroremains in the acid soils of southern subtropical China has hampered understanding of prehistoric diets in the region and of the spread of domesticated rice southwards from the Yangtze River region. According to records in ancient books and archaeological discoveries from historical sites, it is presumed that roots and tubers were the staple plant foods in this region before rice agriculture was widely practiced. But no direct evidences provided to test the hypothesis. Here we p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(55 citation statements)
references
References 21 publications
2
53
0
Order By: Relevance
“…In New Guinea, agricultural dependence and intensification of production can be suggested from 5000 to 3500 B.P., with ditched fields, wooden spades, and probable sedentism (68). A similar timing is suggested for the introduction of rice and possible spread of banana in Southeast Asia (28,69). In northern South America, sedentism associated with tuber crops and other cultivars (squashes, fruit trees, and maize) dates to the Mid-Holocene in different regions (70).…”
Section: Comparing Timing Of Domestication In Vegecultural Cropsmentioning
confidence: 66%
See 1 more Smart Citation
“…In New Guinea, agricultural dependence and intensification of production can be suggested from 5000 to 3500 B.P., with ditched fields, wooden spades, and probable sedentism (68). A similar timing is suggested for the introduction of rice and possible spread of banana in Southeast Asia (28,69). In northern South America, sedentism associated with tuber crops and other cultivars (squashes, fruit trees, and maize) dates to the Mid-Holocene in different regions (70).…”
Section: Comparing Timing Of Domestication In Vegecultural Cropsmentioning
confidence: 66%
“…based on archaeological remains of former cultivation plots on old land surfaces, dramatic degradation of montane rainforest to grasslands, and microbotanical evidence for high frequencies of crop plants (26,27). Plant microremains have also recently allowed recognition of palm (sago) starch consumption in tropical South China (28) and Borneo (23).…”
Section: Advances In the Archaeobotany Of Plant Domesticationmentioning
confidence: 99%
“…In the Yangtze Delta area, economic dependency on rice was preceded by a long period of low intensity rice cultivation during which early farmers also collected and relied heavily on acorns, chestnuts and other wild plants (Zhao and Piperno 2000;Fuller and Qin 2010). By contrast, palaeobotanical evidence suggests that early Neolithic cultures in the Pearl River area depended on the exploitation of wild plants including sago palm, banana, and lotus roots, not rice (Yang et al 2012;Yang et al 2013). When did rice agriculture and the development of ricedependent cultures appear on the Fujian coast?…”
Section: Introductionmentioning
confidence: 99%
“…Previous research on micro-plant remains at the coastal site of Xincun (5300-4500 BP) revealed the importance of palms, roots and tubers in the local plant food exploitation strategy (Yang et al, 2013). This involved management of southern subtropical plants.…”
Section: Canarium Nutsmentioning
confidence: 99%